The coach's perception of the performance of game actions in training sessions. A case study in volleyball - Manzanares, P.; Palao, J. M.; Ortega, E. (International Journal of Performance Analysis in Sport, 2014)
Monitoring training sessions is a key aspect for team sports. This study presents and applies a tool for improving the coach's qualitative analysis of the technical and tactical content. The goal of this study was to compare the coach's subjective evaluation of players' actions in training with the objective evaluation. The tool was applied to analyse two complete weeks of training of the competitive phase (including matches) of a volleyball team from the Spanish men's first division. The study's variables included: a) type of task, b) type of technical action carried out in the task, c) degree of fulfilment of the objectives in the exercises, d) coach's perception, and e) degree of agreement between what is perceived and what is actually carried out. A descriptive and inferential analysis of the data was done. In this sample, the differences between the subjective perception of the coach and the objective recording of the efficacy demonstrate the need for training processes to be constantly monitored and the need for a specific plan for observing and analysing the training processes to increase the quality of the work that is carried out. The benefits, limitations, and usability of the tool are reviewed in the article.